Optical Guided-wave Chemical and Biosensors II - Zourob, Mohammed; Lakhtakia, Akhlesh (Springer Series on Chemical Sensors and Biosensors, Methods and Applications, 2010)
For the first time, distinguished scientists from key institutions worldwide provide a comprehensive approach to optical sensing techniques employing the phenomenon of guided wave propagation for chemical and biosensors. This includes both state-of the-art fundamentals and innovative applications of these techniques. The authors present a deep analysis of their particular subjects in a way to address the needs of novice researchers such as graduate students and post-doctoral scholars as well as of established researchers seeking new avenues. Researchers and practitioners who need a solid foundation or reference will find this work invaluable. This second of two volumes covers the incorporation of periodic structures in waveguides to exploit the Bragg phenomenon, optical fiber sensors, hollow waveguides and micro-resonators as well as a review of the tremendous expansion of terahertz technology for sensing applications.